118 A Vestibular Examination Must Include the 12:00 Region. (1st May 2022) - Yee, A; Uloko, M; Goldstein, I
ABSTRACT: Introduction: The vestibule is an endodermal tissue located on the skin surface between Hart's line at the inner aspect of the labia minora (ectoderm), and the hymen, at the vaginal opening (mesoderm). The vestibule contains the urethral meatus and minor and major vestibular glands. The vestibule releases mucinous lubrication during sexual arousal that is achieved, in part, by vestibular innervation, likely from somatic (pudendal branch) and autonomic (pelvic branch) nerves. As part of an evaluation of patients with entrance dyspareunia, providers should perform a cotton-tip swab test to assess pain intensity and degree of erythema. Typically, the locations assessed are the 1:00, 3:00, 5:00, 6:00, 7:00, 9:00 and 11:00 locations of the posterior and right/left anterior vestibule. This testing strategy, however, does not include the entire vestibule. The 12:00 region of the vestibule is located above the urethral meatus, just below the clitoris and medial to Hart's line. The 12:00 region can also be painful during cotton-tip swab testing. Few providers examine this region or consider it during treatment. Objective: The main objective of this study was to compare the pain scores of cotton-tip swab testing and degree of erythema of the 12:00 region to those of the 1:00, 3:00, 5:00, 6:00, 7:00, 9:00 and 11:00 locations in women presenting with entrance dyspareunia. The secondary objective was to examine the 12:00 region for the presence of minor vestibular glands. Methods: Women presenting to our clinic with complaints of entrance dyspareunia underwent vulvoscopy with photography and cotton-tip swab testing including the 12:00 region while using a vulvoscope (Wallach Zoomscope) with attached camera (Cannon). Pain intensity was rated by the patient (0 – 10), with pain >3 considered clinically significant. Erythema was rated by the provider (absent, mild, moderate or severe) with any erythema considered clinically significant. Results: A total of 144 women (mean age 43 +/- 20, range 13-83 years) underwent vulvoscopy at the standard 1:00, 3:00, 5:00, 6:00, 7:00, 9:00 and 11:00 locations. In addition, they were tested concomitantly at the 12:00 location. Among this group of women, 26 (18%) had absent pain and absent erythema throughout all locations; 25 (18%) had positive findings of pain and erythema in at least 3 of the usual vestibular locations but not at 12:00; and 92 (64%) had pain and erythema in at least 1 of the usual vestibular locations and at 12:00. Photographs revealed 27% of those experiencing pain at the 12:00 had obvious single/multiple ostia of minor vestibular glands at that location. Conclusions: Women with entrance dyspareunia commonly have pain and erythema at the 12:00 region of the vestibule. Photography reveals the presence of minor vestibular glands at the 12:00 location. Providers should examine the entire vestibule including the 12:00 region during examination. Providers should consider including the 12:00 vestibule when treating entrance dyspareunia with medication such as compounded testosterone and estradiol and/or surgery. Disclosure: Work supported by industry: no.